2022
DOI: 10.7554/elife.77393
|View full text |Cite
|
Sign up to set email alerts
|

MCMBP promotes the assembly of the MCM2–7 hetero-hexamer to ensure robust DNA replication in human cells

Abstract: The MCM2–7 hetero-hexamer is the replicative DNA helicase that plays a central role in eukaryotic DNA replication. In proliferating cells, the expression level of the MCM2–7 hexamer is kept high, which safeguards the integrity of the genome. However, how the MCM2–7 hexamer is assembled in living cells remains unknown. Here, we revealed that the MCM-binding protein (MCMBP) plays a critical role in the assembly of this hexamer in human cells. MCMBP associates with MCM3 which is essential for maintaining the leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 56 publications
2
22
1
Order By: Relevance
“…Although it was reported that the interaction of yeast MCM2 3). Recently, it was reported that the MCM-binding protein (MCMBP) binds to Mcm3 through its N-terminal domain, which results in promoting the assembly of MCM2-7 complex in human cells (Saito et al, 2022). iScience Article However, we did not observe both MCMBP and Cdt1 during the preparation of MCM2-7 complex, indicating that the MCM2-7 hexamer is very stable once the six subunits assembled together.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although it was reported that the interaction of yeast MCM2 3). Recently, it was reported that the MCM-binding protein (MCMBP) binds to Mcm3 through its N-terminal domain, which results in promoting the assembly of MCM2-7 complex in human cells (Saito et al, 2022). iScience Article However, we did not observe both MCMBP and Cdt1 during the preparation of MCM2-7 complex, indicating that the MCM2-7 hexamer is very stable once the six subunits assembled together.…”
Section: Discussioncontrasting
confidence: 55%
“…Although it was reported that the interaction of yeast MCM2-7 with ATPγS promotes closure of Mcm2-Mcm5 gate and subsequently Cdt1 stabilizes the Mcm2-Mcm5 gate, only the open ring form of human MCM2-7 is observed after treatment of ATPγS in the absence of Cdt1 ( Figure 3 ). Recently, it was reported that the MCM-binding protein (MCMBP) binds to Mcm3 through its N-terminal domain, which results in promoting the assembly of MCM2-7 complex in human cells ( Saito et al., 2022 ). However, we did not observe both MCMBP and Cdt1 during the preparation of MCM2-7 complex, indicating that the MCM2-7 hexamer is very stable once the six subunits assembled together.…”
Section: Discussionmentioning
confidence: 99%
“…MCM proteins connecting with MCMBP is essential for maintaining the pool of functional MCM2‐7 hexamers. 128 , 129 …”
Section: The Replication Stress Responsementioning
confidence: 99%
“…The MCM‐binding protein (MCMBP) is considered as a chaperone of MCM proteins to assist dynamic assembly of the MCM2‐7 hexamer and promotes MCM8‐9 for HR repair. MCM proteins connecting with MCMBP is essential for maintaining the pool of functional MCM2‐7 hexamers 128,129 …”
Section: The Replication Stress Responsementioning
confidence: 99%
See 1 more Smart Citation